NDUFS4: Creation of a Mouse Model Mimicking a Complex I Disorder - Ingraham, Christopher A. (2009)
The Complex I NADH dehydrogenase-ubiquinone-FeS 4 (NDUFS4) subunit gene is involved in proper Complex I function such that the loss of NDUFS4 decreases Complex I activity resulting in mitochondrial disease. Therefore, a mouse model harboring a point mutation in the NDUFS4 gene was created. An embryonic lethal phenotype was observed in homozygous (NDUFS4 (-/-)) mutant fetuses. Mitochondrial function was impaired in heterozygous animals based on oxygen consumption, and Complex I activity in NDUFS4 mouse mitochondria. Decreased Complex I activity with unaltered Complex II activity, along with an accumulation of lactate, were consistent with Complex I disorders in this mouse model.